Parasites of North American freshwater fishes - Hoffman, Glenn L. (Comstock Pub. Associates, 1999)
The book provides information on public health concerns about fish parasites, the methods used to examine fish for parasites, and those parasites found only in very selective organs or tissues. It lists the known species of each genus, along with reference citations that enable readers to find literature pertinent to species identification, life cycles, and in some cases, control. In the heart of the book, each chapter opens with a description of a phylum and its relevant families and genera, followed by a species list for those genera. Drawings illustrate a representative of each genus, and are supplemented by photographic examples. Many new parasites of North American freshwater fishes have been discovered since the publication of the first edition thirty years ago. For this new edition, the author has added new species accounts and revised the taxonomy, expanded descriptions and discussion of the most important fish parasites, provided a glossary to aid nonspecialists, and updated the reference list through 1992. The volume features twice as many illustrations as the first edition, including the addition of 33 color photographs.